2004
DOI: 10.1063/1.1829784
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between morphological defects, electron beam-induced current imaging, and the electrical properties of 4H–SiC Schottky diodes

Abstract: Defects in SiC degrade the electrical properties and yield of devices made from this material. This article examines morphological defects in 4H–SiC and defects visible in electron beam-induced current (EBIC) images and their effects on the electrical characteristics of Schottky diodes. Optical Nomarski microscopy and atomic force microscopy were used to observe the morphological defects, which are classified into 26 types based on appearance alone. Forward and reverse current–voltage characteristics were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…MPs appear as line segments, of which lengths are dependent on the wafer thickness, the miscut angle, and the sample tilting relative to the beam. The MPs run in different directions instead of lying parallel to the growth direction, similar to the observation described in an earlier paper [32]. In fact, the majority of MPs deviated from the growth direction and inclined toward one another or other defects in all six wafers studied.…”
Section: The Evolution Of Defects During Sic Growthsupporting
confidence: 69%
“…MPs appear as line segments, of which lengths are dependent on the wafer thickness, the miscut angle, and the sample tilting relative to the beam. The MPs run in different directions instead of lying parallel to the growth direction, similar to the observation described in an earlier paper [32]. In fact, the majority of MPs deviated from the growth direction and inclined toward one another or other defects in all six wafers studied.…”
Section: The Evolution Of Defects During Sic Growthsupporting
confidence: 69%
“…When defects are present, breakdown of a device is often accelerated. Recent published results examining how SiC Schottky Barrier diodes (SBD) are influenced by defects have demonstrated that forward and reverse characteristics are sensitive to essentially any defect within the active region of the device [1][2][3][4]. Defects that are known to degrade diode characteristics include micropipes, comets, carrots, inclusions, small-angle boundaries, and screw dislocations.…”
Section: Introductionmentioning
confidence: 99%
“…EBIC has been used to measure minority carrier diffusion length in both 4H-and 6H-SiC [91,92]. It also has been used to characterize electrical active surface defect in 4H-SiC diodes [93,94].…”
Section: Pulsed Mos Capacitor (C-t)mentioning
confidence: 99%